Graphene Oxide Derivatives and Their Nanohybrid Structures for Laser Desorption/Ionization Time-of-Flight Mass Spectrometry Analysis of Small Molecules - Seung-Woo Kim; Sunbum Kwon; Young-Kwan Kim (Nanomaterials, 2021)
Matrix-assisted laser desorption/ionization (MALDI) has been considered as one of the most powerful analytical tools for mass spectrometry (MS) analysis of large molecular weight compounds such as proteins, nucleic acids, and synthetic polymers thanks to its high sensitivity, high resolution, and compatibility with high-throughput analysis. Despite these advantages, MALDI cannot be applied to MS analysis of small molecular weight compounds (<500 Da) because of the matrix interference in low mass region. Therefore, numerous efforts have been devoted to solving this issue by using metal, semiconductor, and carbon nanomaterials for MALDI time-of-flight MS (MALDI-TOF-MS) analysis instead of organic matrices. Among those nanomaterials, graphene oxide (GO) is of particular interest considering its unique and highly tunable chemical structures composed of the segregated sp2 carbon domains surrounded by sp3 carbon matrix. Chemical modification of GO can precisely tune its physicochemical properties, and it can be readily incorporated with other functional nanomaterials. In this review, the advances of GO derivatives and their nanohybrid structures as alternatives to organic matrices are summarized to demonstrate their potential and practical aspect for MALDI-TOF-MS analysis of small molecules.